P264 Bridging the gap: co-producing a virtual self-management programme for individuals living with axial spondyloarthritis. (23rd April 2022) - Clark, Zoe E; Gregory, Will; Chan, Antoni; Coy, Aisling; Cox, Zoe; Dickinson, Sally; Gaffney, Karl; Harrison, Beverley; Herbert, Helena; Lewis, Claire; McCoy, Catherine; Noel, Katharine; et al.
Abstract: Background/Aims: Despite the considerable impact axial spondyloarthritis (axSpA) has on quality of life, condition-specific group education programmes are not routinely offered. Many people with axSpA report feeling isolated and often have never met anyone else with the condition. In 2020, the National Axial Spondyloarthritis Society (NASS) worked with patients and rheumatology departments to co-produce a pilot self-management programme (SMP) to explore demand from and assess the impact on patients and healthcare professionals (HCPs). Methods: NASS identified six NHS centres to host the pilot SMP sessions. These centres represented a range of axSpA services. HCPs invited their axSpA cohort to attend by post or e-mail and NASS invited local NASS members. Attendees booked online via private URL. NASS developed content following consultation with rheumatology HCPs and people living with axSpA. The first session covered pain, flares, fatigue and emotional wellbeing. Following attendee feedback, three centres hosted a second session on medication and exercise. One centre held a third session covering night pain, sleep and stress. Sessions were delivered via online meeting software and included teaching, group discussions, polls and exercise. HCPs of the host rheumatology departments led these sessions in tandem with NASS staff, one of whom has lived experience of axSpA. Content and format were continually reviewed and improved using feedback from attendees and HCPs (Table 1 ); feedback was gathered by email, informal focus groups and anonymous surveys. Results: A total of 266 patients attended. 55% were female and 27% were aged under 45. 10% were diagnosed within the past year; 26% within the last 5 years; >50% more than 10 years ago. No attendees had previously attended a hospital axSpA SMP session. Conclusion: There is demand from patients and HCPs for an axSpA virtual patient SMP. Co-producing the programme can be effective for: engaging with a range of patients; educating and empowering patients to self-manage their condition; building relationships between HCPs and patients; reducing patient isolation; enabling appropriate self-referral to rheumatology services. This pilot has informed our next steps to expand the online sessions to new centres and explore co-producing an e-learning programme. Disclosure: Z.E. Clark: Grants/research support; National Axial Spondyloarthritis Society receives grant funding from AbbVie, Biogen, Eli Lilly, Janssen, Novartis, UCB. W. Gregory: Honoraria; Speaker, conference registration and advisory board fees from AbbVie, Pfizer, Novartis, UCB. A. Chan: Member of speakers' bureau; UCB, Novartis, Sanofi, AbbVie, Jannsen. A. Coy: None. Z. Cox: None. S. Dickinson: Grants/research support; National Axial Spondyloarthritis Society receives grant funding from AbbVie, Biogen, Eli Lilly, Janssen, Novartis, UCB. K. Gaffney: Shareholder/stock ownership; SpA Academy. Honoraria; Novartis, AbbVie, UCB, Lilly, Pfizer, Biogen. Member of speakers' bureau; Celltrion, Novartis, UCB, AbbVie. Grants/research support; NASS, AbbVie, Pfizer, UCB, Novartis, Lilly, Jannsen, Gilead, Biogen. Other; Meeting expenses: AbbVie, Lilly, Roche, Novartis, Pfizer, UCB. B. Harrison: None. H. Herbert: None. C. Lewis: None. C. McCoy: None. K. Noel: None. K. Porthouse: None. K. Rigler: None. K. Weight: None. T. Williams: None. D. Webb: Grants/research support; National Axial Spondyloarthritis Society receives grant funding from AbbVie, Biogen, Eli Lilly, Janssen, Novartis, UCB. L. Dunkley: Honoraria; Honoraria with UCB, AbbVie, Pfizer.